Small happiness with a flower every week : ReFlower's joy and sorrow in creating customer value - Li, Dongxian, (SAGE business cases, 2018)
In the season of blooming flowers, Zhu Yueyi looked at the colorful flowers around and recalled the days and nights since the start of the business. Besides joy, she also felt a certain worry. Her joy is because of the achievements made. As an e-commerce that provides customers with weekly, monthly, quarterly, and annually flower ordering and themed flower delivery services through the WeChat public account, ReFlower has accumulated almost 100,000 users by word of mouth and achieved a monthly turnover of several million Yuan in less than 10 months from August 2015. Regarding her worry, as more and more enterprises poured into this market, the products became highly homogenized, and the resulting vicious price competition had a great impact on ReFlower. The way out for the future inevitably caused concern and pondering for Zhu Yueyi.